Neuronal ceroid lipofuscinosis type 2: an Australian case series. (24th April 2020) - Johnson, Alexandra M; Mandelstam, Simone; Andrews, Ian; Boysen, Katja; Yaplito‐Lee, Joy; Fietz, Michael; Nagarajan, Lakshmi; Rodriguez‐Casero, Victoria; Ryan, Monique M; Smith, Nicholas; Scheffer, Ingrid E; Ellaway, Carolyn
Abstract : Aim: Late infantile neuronal ceroid lipofuscinosis type 2 (CLN2) disease is a rare neurodegenerative disorder presenting in children aged 2–4 years with seizures and loss of motor and language skills, followed by blindness and death in late childhood. Initial presenting features are similar to a range of common epilepsies. We aim to highlight typical clinical and radiological features that may prompt diagnosis of CLN2 disease in early disease stages. Methods: We present a series of 13 Australian patients with CLN2 disease, describing clinical features, disease evolution, neuroimaging, electroencephalogram, biochemical and genetic results. Expert neuroradiological magnetic resonance imaging (MRI) analysis was retrospectively performed on 10 cases. Results: Twelve patients presented with seizures, with initial seizures being focal ( n = 4), generalised tonic–clonic ( n = 3), absence ( n = 3) and febrile ( n = 2). Eleven patients (85%) had a language delay before the onset of seizures. Cerebellar or cerebral atrophy was noted in all patients on centralised MRI review, with abnormalities of the brain‐stem, ventricles, corpus callosum and hippocampi. Conclusions: Early language delay with the onset of seizures at 2–4 years of age is the hallmark of CLN2 disease. MRI findings of early subtle atrophy in the cerebellum or posterior cortical regions should hasten testing for CLN2 disease to enable early initiation of enzyme replacement therapy. Abstract : Translation into Japanese Translation into Chinese